2015
DOI: 10.1021/jacs.5b08482
|View full text |Cite
|
Sign up to set email alerts
|

Sialic Acid-Imprinted Fluorescent Core–Shell Particles for Selective Labeling of Cell Surface Glycans

Abstract: The expression of cell surface glycans terminating with sialic acid (SA) residues has been found to correlate with various disease states there among cancer. We here report a novel strategy for specific fluorescence labeling of such motifs. This is based on sialic acid-imprinted core-shell nanoparticles equipped with nitrobenzoxadiazole (NBD) fluorescent reporter groups allowing environmentally sensitive fluorescence detection at convenient excitation and emission wavelengths. Imprinting was achieved exploitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
219
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 225 publications
(227 citation statements)
references
References 30 publications
4
219
0
4
Order By: Relevance
“…This calls for the development of alternative glycan-specific probes and cell imaging technologies. Recent reports have shown that synthetic probes based on host guest chemistry [10] or molecular imprinting technology [11] can be used for glycan selective staining of cells and tissues. Using the former approach, Xu and colleagues developed fluorescent sensors based on two boronic acids linked to a functionalized peptide for detection of cell-surface cancer-associated glycans [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This calls for the development of alternative glycan-specific probes and cell imaging technologies. Recent reports have shown that synthetic probes based on host guest chemistry [10] or molecular imprinting technology [11] can be used for glycan selective staining of cells and tissues. Using the former approach, Xu and colleagues developed fluorescent sensors based on two boronic acids linked to a functionalized peptide for detection of cell-surface cancer-associated glycans [10].…”
Section: Introductionmentioning
confidence: 99%
“…In flow cytometry and fluorescence microscopy investigations, the SA-MIP selectively targeted two different prostate cancer cell lines DU145 and PC3, as well as the T leukemia cell line Jurkat. The SA expression was verified with lectin-FITC [11]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, NPs of MIP imprinted with melittin (a component of bee venom) injected into mouse protected the animal from the bee venom [77]. Moreover, NPs of SiO 2 coated with a sialic acid (SA)-imprinted MIP film bearing nitrobenzoxadiazole (an organic dye) moieties in the polymer matrix were prepared [45]. These NPs were used for fluorescent labeling cells with SA-terminated glycan motifs on their surface.…”
Section: Miscellaneous Applicationsmentioning
confidence: 99%
“…xx, No. yy 7 acid 16[36][37][38][39], 4-vinylphenylboronic acid 17[40][41][42][43][44][45], 3-acrylamidophenylboronic acid 18[46], and [ 1 9 _ T D $ D I F F ] 2,2 0 -bithiophene-5-boronic acid 19[47,48], as functional monomers. The boronic acid group reversibly forms esters with two adjacent hydroxyl groups of vicinal diols and catechols.…”
mentioning
confidence: 99%
See 1 more Smart Citation